Mississippi Delta Restoration Pathways to a sustainable future (Estuaries of the World,, 2018)
This book is a new and provocative treatment dealing with and defining sustainable pathways for the restoration of the Mississippi Delta. Based on a consideration of natural functioning of the Mississippi delta, factors that led to its severe deterioration, and major global trajectories of the 21st century, the authors investigate possible future pathways for sustainable management of the delta. They consider current conditions as well as future trajectories of climate and energy and resource scarcity. The book concludes that without profound changes of how humans live in and manage the delta, sustainability of the delta will be profoundly compromised.